Pengembangan Media Pembelajaran Berbasis Google Classroom pada Materi Pokok Jenis-Jenis Alat Berat pada Pekerjaan Konstruksi - Zai, Fatiyaaro; Telaumbanua, Aprianus; Telaumbanua, Arisman; Harefa, Envilwan Berkat (Jurnal Suluh Pendidikan, 2024)
The problems faced by students of class X DPIB SMK Negeri 1 Lotu are limited discussion space, difficulty in understanding the material, and low interest in various heavy equipment used in construction, caused by the use of conventional teaching methods. Previous research has shown that Google Classroom is effective in enhancing learning compared to traditional teaching methods. The development of Google Classroom-based learning media is expected to assist students in understanding the various types of heavy equipment used in construction. This research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) using questionnaires, observations, interviews, and tests as research instruments. The validity of this learning media is validated by three validators: media experts (score 75.29%), language experts (score 86.67%), and subject matter experts (score 86%). Based on these assessments, it can be concluded that Google Classroom-based learning media on the subject of various types of heavy equipment in construction are valid and suitable for use. This media is practical in its application and effective in enhancing student learning outcomes. Overall, this research produces learning media that are valid, practical, and effective.